An Insight into the Educational Buildings of the First National Architecture Period in Turkey Based on Egli’s Architectural Design Language: Development of a Grammar-Based Model - Beyhan Elhaman; Serkan Palabıyık (Buildings)
The objective of this study is to analyse the principles of educational buildings in the First National Architectural style in Turkey by examining the works of Ernst A. Egli, who is considered one of the pioneers of the modernisation process during the National Architecture Period. To this end, shape grammar was selected as the most appropriate method, as it offers the potential to analyse design languages and produce similar or hybrid designs within this language. The method was first developed by Stiny and Gips in the 1970s with the objective of defining design rules through an algorithmic process. In line with this methodological framework, the study employed a typological analysis of Egli’s educational buildings to derive shape grammar rules. These rules were then presented as input to the design process, with a hybrid application that explores potential design alternatives in accordance with Egli’s design approach by adopting parametric modelling methodology. The findings of the study are discussed comparatively with the buildings of other architects of the period. In this context, the analysis of Egli’s buildings reveals that his designs are compatible with the contemporary architects of his period. Accordingly, a design language that reflects the characteristic features of the First National Architecture Period is presented.